Evaluation of Aortic Zone 2 Proximal Landing Accuracy During Thoracic Endovascular Aortic Repair Following Carotid-Subclavian Revascularization. (May 2021) - Choi, Sally H. J.; Yang, Gary K.; Baxter, Keith; Gagnon, Joel
Background: Adequate seal for thoracic endovascular aortic repair (TEVAR) commonly requires landing in zone 2, but can prove to be challenging due to the tortuous and angulated anatomy of the region. Objectives: Our objective was to determine the proximal landing accuracy of zone 2-targeted TEVARs following carotid-subclavian revascularization (CSR) and its impact on clinical outcomes. Methods: Retrospective review of patients that underwent CSR for zone 2 endograft delivery at a tertiary institute between January 2008 and March 2018 was conducted. Technical outcomes were assessed by examining the incidence of intraoperative corrective maneuvers, 1a endoleaks and reinterventions. Distance to target and incidence of LSA stump filling were examined as radiographic markers of landing accuracy. Results: Zone 2-targeted TEVAR with CSR was performed in 53 patients for treatment of dissections (49%), aneurysms (30%) or trauma (21%). Nine (17%) cases required intraoperative corrective procedures: 5 (9%) proximal cuffs due to type 1a endoleak and 4 (8%) left common carotid artery (LCCA) stenting due to inadvertent coverage. Cases performed using higher resolution hybrid fluoroscopy machine compared to mobile C-arm were associated with increased proximal cuff use (OR 8.8; 95% CI 1.2-62.4). Average distance between the proximal edge of the covered graft to LCCA was 8 ± 1 mm and larger distances were not associated with higher rates of 1a endoleak. Twenty-eight (53%) cases of antegrade LSA stump filling were noted on follow-up imaging, but were not associated with higher rates of reinterventions (OR 0.8, 95% CI [0.2-4.6]). Three (6%) patients had a stroke within 30 days and 4 (8%) patients expired within 1 month. Intraoperative corrective maneuvers, post-operative 1a endoleak and reinterventions were not associated with higher rates of stroke or mortality. Conclusion: Using current endografts and imaging modalities, zone 2-targeted TEVARs have suboptimal technical accuracy.